ANALISIS STRATEGI PEMBELAJARAN PADA MATA KULIAH PERSPEKTIF GLOBAL BERDASARKAN PERSEPSI MAHASISWA PGSD SEMESTER IV KELAS D UNIVERSITAS NUSA CENDANA - Jati Lamauran Koten, Gaudensius; Devidce Mbolik, Margret; Efinda Saputri, Matilda; Djogo Sena, Nathalia; Banola, Serentin; Wonda, Hiwa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe learning strategies in the Global Perspective course based on the perceptions of fourth-semester PGSD (Primary School Teacher Education) students, Class D, at Universitas Nusa Cendana. A quantitative descriptive approach was employed, with data collected from 29 students using a closed questionnaire on a four-point Likert scale. The instrument covered six indicators: learning approach, teaching methods, instructional media, learning interaction, student engagement, and classroom management. All 24 items were declared valid (r > 0.367) and reliable (Cronbach's Alpha: 0.819–0.899). Descriptive statistics computed via SPSS show that all six indicators fall in the "Very Good" category (mean range 3.26–4.00), with an overall mean of 3.453. Learning approach and learning interaction scored highest (3.612 each), while instructional media scored lowest (3.336), though still "Very Good." These findings indicate students positively perceived the applied learning strategies as student-centered, interactive, and conducive. Recommendations include enriching technology-based instructional media and project-based/problem-based learning models to further enhance student engagement and global citizenship competencies.